A comparative study on antimicrobial susceptibility of campylobacter spp. Isolates from fecal samples of domestic animals and poultry in Tonekabon and Shiraz, Iran - Ghane, Masood; Bahador, Nima; Baserisalehi, Majid; Eghbali, Mina (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->During the past decade Campylobacter has been shown to be responsible for enteritis in human and animal. The natural habitats of most Campylobacter species are the intestines of birds and other warm-blooded animals. These organisms may enter the environment, including drinking water, through the feces of animals, birds or infected humans. Fecal samples of Domestic Animals and Poultry were subjected to survey frequency of occurrence of pathogenic Campylobacter spp. in Tonekabon and Shiraz. Antimicrobial susceptibility of the isolates was assessed to evaluate the rate of antibiotic resistant campylobacter’s in both cities. The method for isolation of pathogenic Campylobacter spp. was Kapandis Baseri (prêt-KB) and for antimicrobial susceptibility of the isolates was disk diffusion and E-test. A total of 28 and 37 Campylobacter spp. were isolated in Tonekabon and Shiraz, respectively. All pathogenic Campylobacter spp. isolates were sensitive to Ciprofloxacin, however, varied responses to other antibiotics have been observed among the isolates. In addition, lowest MIC values were found for Ciprofloxacin and Gentamicin and highest MIC values were found for Erythromycin, Chloramphenicol, Gentamicin and Tetracycline. Overall, based on our observations, domestic animals and poultry should be considered as reservoirs of Campylobacter spp. in both cities. Although, frequency of existence of antibiotic resistance Campylobacter in Tonekabon was relatively high, Ciprofloxacin resistant Campylobacter were isolated neither from Tonekabon nor Shiraz. The Result obtained from data statistical analyses showed significant correlation (P<0.05) between the isolation rate of susceptible strains of Campylobacter to Cefalexin, Cefalotin and Ampicillin in Tonekabon and Shiraz.